(untitled) (Journal of Medical & Health Sciences Review, 2025)
Early childhood malnutrition remains a severe global health concern, disproportionately impacting low- and middle-income nations. This research assesses the impact of community-based interventions (CBIs) to alleviate malnutrition in children under five years old. With a mixed-methods research design in rural and peri-urban areas, the study integrates quantitative anthropometric measurements and qualitative interviews. Findings indicate that children who are exposed to CBIs have much lower stunting, wasting, and underweight levels, and attain greater dietary diversity and exclusive breastfeeding compliance than non-exposed children. Community empowerment, culturally acceptable education, and high trust relations with community health workers are highlighted as the major enablers of success by the study. Sustained barriers such as food insecurity and funding uncertainty call for integrated, adaptive, and sustainable models. This study reaffirms the position of CBIs as change agents in child nutrition and demands multi-sectoral coordination and long-term coping strategies to optimize their impact.